Providing healthcare under ISIS: A qualitative analysis of healthcare worker experiences in Mosul, Iraq between June 2014 and June 2017. Issue 10 (3rd October 2019) - Michlig, Georgia J.; Lafta, Riyadh; Al-Nuaimi, Maha; Burnham, Gilbert
ABSTRACT: During ISIS occupation of the Northern Iraqi city of Mosul between June 2014 to June 2017, healthcare workers remaining in Mosul continued to provide medical services. Little is currently known about Iraqi healthcare workers' personal and professional lives in the ISIS healthcare system, and how these individuals adapted. This study sought to explore their experiences during occupation through thematic analysis of qualitative data from twenty interviews conducted immediately after ISIS withdraw from Mosul in August 2017. Participants were sampled from healthcare facilities still in operation after liberation and included healthcare workers of varying disciplines, age and gender. Participants described major changes to their personal and professional lives under ISIS and an extremely limited perceived ability to negotiate the challenges of providing healthcare in the ISIS system. They described terrifying working environments, the strict separation between the sexes, restricted movement, and continuous monitoring by the Al-Hesba morality police. Infractions of ISIS law and subsequent punishment, deaths and kidnappings, changes in personal relationships, poverty and the disrupted schooling of children were also discussed. The importance of protection by supervisors, access to additional money and transportation were highlighted. Understanding these hardships may help support the recovery of health workers experiencing similar situations. Abbreviations: HCW: Healthcare Worker; PHCCs: Primary Health Care Clinics; ISIS: Islamic State of Iraq and Syria